EFEKTIFITAS PENGGUNAAN FRUIT TRAP BERBAHAN NANAS DAN BERBAGAI WARNA LAMPU SEBAGAI PERANGKAP KUMBANG TANDUK (Oryctes rhinoceros) PADA TBM KELAPA SAWIT (Elaeis guineensis Jacq.) - Ridho Hidayatullah Margolang; Hikmah Sejati; Tuty Ningsih; Sulthon Parinduri (Institut Teknologi Sawit Indonesia, 2022)
Oil palm plantations are often damaged by pests, especially the horn beetle (Oryctes rhinoceros) The damage caused can potentially suffer losses, either directly or indirectly. This study aims to determine the effectiveness and intensity of the horn beetle catch obtained by combining fruit traps with various colors of lights in the Immature Plants (TBM) area, the lights used are 18 watt emergency lights. This study used a non- factorial Randomized Block Design (RAK) research method with five levels of treatment, namely: P0 (white light + pineapple), P1 (yellow light + pineapple), P2 (blue light + pineapple), P3 (green light + pineapple). . light + pineapple). light + pineapple). , P4 (red light + pineapple) with four replications to obtain 20 treatment samples. The parameter observed was the number of beetles (O. rhinoceros) trapped. The results of this study showed that P1 was significantly different from treatment P2, P3 and P4 but not significantly different from treatment P0, in general, treatment P1 was the most effective treatment with the acquisition of horn beetles trapped as many as 146 tails. This is because yellow light has a color spectrum length of 560-590 nm which best corresponds to the wavelength of the color spectrum that is acceptable to insects, which is 300-650 nm. In addition, yellow light is more unified and gives a more dominant light reflection in the dark.